Tinjauan Sosiologi Hukum Terhadap Perkawinan Usia Dini (Pandangan Hakim Pengadilan Agama Surabaya) - Ade Setia Yuwandana; Fitrotin Jamilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Judging from the observations that occurred in the city of Surabaya, at the Surabaya Religious Court judges often handle cases of marriage dispensation, so that the practice of early marriage is increasingly paraded. This makes researchers jump into the field to see sociological symptoms that occur in society. From the progress of a written and unwritten law or customary law, making people have different views regarding marriage at an early age. Some marry at an age sufficient to obey the Marriage Law and some marry at an early age as successors to custom. What the community needs to know, in the practice of early marriage that often occurs in social, will have a bad impact. Thus, the community needs to examine the causal factors in early marriage. Related to this, the purpose of this thesis was raised to find out the sociological review of law on early marriage in Surabaya, and causal factors in early marriage in Surabaya. Type of Method used Qualitative. And using the judge's interview technique as a resource person and supported by literature as a thesis support.